Anopheles gambiae on remote islands in the Indian Ocean - Ditter, Robert E. (2023)
Funding Information: We thank the National Malaria Control Program personnel from the Union of the Comoros for facilitating field collections in the islands. We thank the team of the Medical Entomology Unit of the Institut Pasteur de Madagascar for collecting and processing specimens from Madagascar. Funding Information: This work was supported by grants from the UC Irvine Malaria Initiative Program (A17- 0209) and Open Philanthropy (A20-3521). Publisher Copyright: © 2023, The Author(s).